The Politics Settlement of Land Tenure Conflicts During Jokowi’s Presidency (Universitas Negeri Semarang, 2022)
This study was prompted by the high rate of land tenure conflicts in forest areas. In the 2015-2020, a total of 10,000 conflicts were experienced in Indonesia, and a legal approach was used to conduct this normative study. Furthermore, the data collection was through literature and the legal norm method was used for analysis. The results showed that the government reduced the treatment of the conflict by establishing the Directorate of Customary Forest Tenure Conflict Management institutions and legal products of Presidential and Ministerial Regulations. However, the forest land tenure conflict was not resolved during the Joko Widodo administration and was increased by 50 percent from the previous administration of President Susilo Bambang Yudhoyono. Meanwhile, this conflict can be resolved through the role affirmation of State Administrative Law in determining forest areas with legal certainty and justice. The assertion was conducted by enforcing this law against licensing violations and building integrated conflict resolution in creating legal certainty and equity.